2005
DOI: 10.1007/s00383-005-1584-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of moderate hypothermia on energy metabolism and serum inflammatory markers during laparotomy

Abstract: The objective of this study was to investigate energy metabolism of the gut and liver as well as serum inflammatory cytokines following exploratory laparotomy at moderate hypothermia. Two groups of rats were studied, (n=6-8/group); laparotomy at normothermia for 120 min and laparotomy at hypothermia (32-33 degrees C) for 120 min. Study 1: Intestinal glucose, succinate, lactate, phosphocreatine, and ATP as well as hepatic glucose, succinate, lactate, and ATP were measured in terms of micromole per gram using ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Up until now there is no consensus about the best level of temperature which should be applied, but a set of evidences points that a mild or moderate hypothermia is able to confer protection to the liver 4,17,18 . The main mechanism of protection postulated is a decrease of cellular metabolism and oxygen requirement, which occurs consequent to hypothermia, preserving energy and allowing a longer period of inflow occlusion 5,17,19 . However, the IPC also has been related to a lesser demand of energy and this is one of the mechanisms attributed to the liver protection 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up until now there is no consensus about the best level of temperature which should be applied, but a set of evidences points that a mild or moderate hypothermia is able to confer protection to the liver 4,17,18 . The main mechanism of protection postulated is a decrease of cellular metabolism and oxygen requirement, which occurs consequent to hypothermia, preserving energy and allowing a longer period of inflow occlusion 5,17,19 . However, the IPC also has been related to a lesser demand of energy and this is one of the mechanisms attributed to the liver protection 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Even with the strong evidence of benefits in the liver and other target-organs 21 , the use of body hypothermia has been limited because the risks of inducing hemodynamic disturbances, coagulopathy, metabolic acidosis and arrhythmias 19 . In addition, the technique of in situ liver perfusion is complex, demanding total vascular exclusion and veno-venous by-pass 7,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional research in the same model has shown that hypothermia decreases the elevation of serum soluble intercellular adhesion molecule-1 (sICAM), presuming that hypothermia blunts tissue injury 22. Moderate hypothermia in the rat NEC model during laparotomy does not appear to affect energy metabolism 23. Finally, an animal model of intestinal ischemic and reperfusion with mild hypothermia to 32 to 33.0°C decreases intestinal injury and other organ dysfunction 24.…”
Section: Necrotizing Enterocolitis and Mild Hypothermiamentioning
confidence: 99%